Adsorption of Di-butylester of Sodiumsulpho Succinic Acid at the Hydrocarbon Mixture-Water Interfaces - KUMARI BAGHEL, HEMA; SINGH, L.R. (Asian Journal of Chemistry, 2010)
A modified drop volume technique was used for measuring interfacial tension (γ) at mixture containing entire mole fraction range of benzene in benzene and toluene-water interfaces with varying concentration of di-butylester of sodiumsulpho succinic acid (BSS) at 27°C using AGLA micrometer syringe (Burroughs Wellcome). It has been observed that there was regular decrease in interfacial tension with increase in concentration of BSS. From the data of interfacial tension at various concentration of surfactant, γ-log C curves were plotted. The values of surface excess, Γs, have been calculated from the gradients of γ-log C curves using appropriate form of Gibb's adsorption equation. From these data, number of surfactant ions adsorbed per cm2 of interface and the area occupied per surfactant ion have been estimated. The area corresponding to closest packing of monomolecular film was determined by extrapolation of π-A curves back to zero surface pressure. It has been observed that as the mole fraction of benzene in mixture of benzene and toluene increases, the value of interfacial tension decreases and area corresponding to closest packing of mono-molecular film of BSS increases.